The psychology of mass persuasion - Human Relations Media, inc. (Pleasantville, NY : Human Relations Media, 1987)
Presents an analysis of mass persuasion in modern society by examining the psychosocial aspects of persuasion, the ways that attitudes are formed and changed, and the methods and ethics of propaganda
pt. 1. Attitudes and attitude change -- pt. 2. Buyers and sellers -- pt. 3. Propaganda.
Keywords: Persuasion (Psychology); Attitude change; Propaganda